Communicating the Message Analysis on Tiktok @Huseinjafar to Maintain Interfaith Tolerance - Aep Wahyudin (Lingkar Studi Komunikasi (LISKI), 2023)
Tiktok has become one of the most popular social media for many Indonesian young millennials. They seek the content at Tiktok mostly for their daily references. Husein Ja’far Al Hadar, a trending moslem scholar utilized Tiktok to deliver the message of inter religious dialogue. We analyzed one short video content using semantic method on Tiktok @huseinjafar which only contained the conversation among Islam, Christian and Buddhist. They talked about their perspectives on tolerance. The finding shown that the harmonious interreligious dialogue could bring the mutual understating when it communicated in peaceful way. The constructive communication process of their dialogue in the video brought the message of living in harmony and respecting each other toward the differences. Tiktok @huseinjafar wanted to deliver the true message of human values by worshiping God and the loving all mankind to shape harmonious interreligious environment. Keywords:, Communicating, Tolerance, Human Values, Tiktok